Analysis of Urban Sprawl Dynamics Using Geospatial Technology in Ranchi City, Jharkhand, India - Ahmad, Firoz; Goparaju, Laxmi (Journal of Environmental Geography, 2016)
The availability of remote sensing satellite data at various spatial, temporal and spectral resolutions provides enormous opportunity to map the urban sprawl. When coupled with Geographic Information System (GIS) it is possible to evaluate, analyse and integrate large data. We need to understand and quantify the urban sprawl on spatial and temporal scales which forms a basis for better planning and sustainable management of cities and towns. The city of Ranchi has witnessed unprecedented urban growth after assuming the status of a capital of Jharkhand state, India in 2000. The increasing population has put pressure on the natural resources of the city. The urban growth has been in a haphazard manner at the cost of agricultural lands, forest land and open green spaces such as park, garden and recreational forestry. The present study analysed the urban sprawl in Ranchi city, using Landsat data from 1976, 2002 and 2015. The study revealed that the annual urban growth rate was 1.76 ha/yr over the period from 1976 to 2002 whereas the annual growth rate was 2 ha/yr over the period from 2002 to 2015. The northern side of the city has witnessed more expansion in 2002 when compared with the growth in 1976. Increase in urban density was seen at the distances of 3, 4,5,6,7 and 8km between 1976 and 2015 and the rate was higher than 25%.The driving factors of the development were infrastructure, educational and business expansion. Thus, spatial analyses of urban sprawl are a prerequisite for curbing the unplanned urban growth and ensure sustainable living.